1994
DOI: 10.1002/stem.5530120609
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of human cord blood progenitor cell growth by recombinant human interleukin 3 (IL‐3), IL‐6, granulocyte‐macrophage colony stimulating factor (GM‐CSF) and stem cell factor (SCF) in serum‐supplemented and serum‐free medium

Abstract: a) day-14/day-7 CFU-GM ratio was higher in CB than in BM indicating that CB CFU-GM are more primitive than BM CFU-GM; b) FCS can be successfully replaced by serum-free medium; c) FCS contains inhibitors of day-14 CFU-GM and among them TGF-beta; and d) the association IL-3, SCF, GM-CSF and IL-6 seems able to totally overcome the inhibitory effect of FCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
3
6
0
Order By: Relevance
“…Previous studies have demonstrated that HUCB HPC seem to be more primitive than their counterparts in BM or peripheral blood [32][33][34][35][36][37][38][39][40][41][42][43][44]. In the present study, we have demonstrated that the anti-HIV agents IFN-␣ and ARA-C have a greater effect on BM HPC than HUCB HPC.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Previous studies have demonstrated that HUCB HPC seem to be more primitive than their counterparts in BM or peripheral blood [32][33][34][35][36][37][38][39][40][41][42][43][44]. In the present study, we have demonstrated that the anti-HIV agents IFN-␣ and ARA-C have a greater effect on BM HPC than HUCB HPC.…”
Section: Discussionsupporting
confidence: 58%
“…The hematopoietic progenitors in HUCB seem to be more primitive than their counterparts in BM or peripheral blood: The colonies in agar or methyl cellulose are bigger and the multipotential colony-forming units (CFU-Mix) and highly proliferative potential colony-forming cells (HPP-CFC) are more numerous. Compared to adult BM stem cells, the cells survive longer and expand with different growth factors in longterm cultures [32][33][34][35][36][37][38]. Integration of retroviruses or adeno-associated viruses is more effective in HUCBenriched progenitor cells than in adult BM [39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…We considered that to be useful for adult stem cell transplantation, a CB sample should be expanded by at least fourfold (11). In the present study, only 11 of 23 CB samples responded with such an expansion.…”
Section: Discussionmentioning
confidence: 83%
“…The expansion of progenitor cells was heterogeneous, with CD34+ cell expansion ranging from 0 to 309-fold and CD34+CD38-cell expansion ranging from 0 to 45fold. Considering that a nonexpanded CB sample can be used to safety transplant a 20-kg body recipient (11), the progenitor cell expansion required for an acceptable adult graft would be in excess of fourfold. We have chosen, in this study, to take into account for evaluation of the expansion only CB samples in which the CD34+ cell expansions were greater than fourfold and thus could be useful for clinical application.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation